Mapping of the Somatosensory Cortex - Jahangiri, Faisal R (Cureus, 2020)
Intraoperative sensory cortical mapping is a reliable and safe method for the functional localization of the central sulcus (CS). It is utilized during neurosurgical procedures performed near eloquent brain tissue. It helps in identifying the somatosensory cortex and CS, hence preventing any postoperative neurological deficits. When executed properly, this method can identify the somatosensory cortex for both the upper and lower limbs by locating the CS. This technical report outlines the benefits of cortical sensory mapping (CsM) and detailed methodology. With the help of a properly trained intraoperative neuromonitoring staff who can accurately interpret the signals being monitored, CsM can help in injury prevention during brain surgeries.